PENGARUH PENDAPATAN ORANG TUA TERHADAP TINGKAT PENDIDIKAN ANAK DI KANAGARIAN LUBUK TARANTANG KECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - Vella Septika; Rahmanelli Rahmanelli (JURNAL BUANA, 2021)
ABSTRACK This study aims to obtain data and discuss the effect of parents’ income on the level of education of children in kanagarian Lubuk Tarantang. This study uses an associative descriptive method. The sample technique used is the random sampling. The number of samples studied was 43 households. Held in june 2020. Data collection methods through the method of documentation and questionnaire methods. Data analysis techniques using the product moment formula. The results of the study are r count 0,31 greater than r table in a significant level of 5% namely 0,31> 0,30. So that the alternative hypothesis in this study is accepted. Based on the results of the t test, it is obtained that the t value is 2,199 which is greater than tke t table 2,019. It is known that parents’ income has a significant effect on children’s education level. Keywords : income, level of education